DEVELOPMENT OF THE INDONESIAN MILITARY’S WORK-LIFE BALANCE SCALE - Freddy Andri Simanjuntak; Urip Purwono; Eri R. Hidayat (The Republic of Indonesia Defense University, 2020)
Work-life balance is important for individual psychological well-being, including for Indonesian soldiers in the UN Peacekeeping mission. Balancing these two factors will positively affect psychological well-being. Fisher, Bulger, & Smith once stated that when work interface with life it can affect work-life balance. Critical to individual psychological well-being as it is, scale developed to assess this construct in the Indonesian military population has never been reported. This study was aimed at examining the validity and reliability of a work-life balance scale specifically developed for use in Indonesian military population in the operation field. This study seeks to confirm the underlying dimensions of work-life balance by testing the hypnotized model employing Confirmatory Factor Analysis (CFA). The participants consist of 100 Indonesian soldiers. The results show that the work-life balance scale (25 items) has a high reliability (α = 0.889). Further analysis resulted that the model was fit to the data (X2 = 248.37; p = 0.092; RMSEA = 0.035; CFI = 0.98; and SRMR = 0.068). It was concluded that the 4 dimensions were the four major valid dimensions, and this study indicate that testing the model using multigroup samples of different demography as well as rank and cultural background is warranted.